PROSES PEMBUNGAAN BEBERAPA VARIETAS Hoya coronaria DARI KAWASAN HUTAN KERANGAS AIR ANYIR, BANGKA - Risti Annisa; Yulian Fakhrurrozi; Sri Rahayu (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2017)
Hoya coronaria found in heath forest of Air Anyir, Bangka has diverse colors. Flowers color diversity sometimes correlated varieties or the result of color changes during flowering process. The flowers development process observed from 5 H. coronaria varieties with different color from heath forest of Air Anyir, Bangka.The purpose of this research to know the flowering process and flower color change process some varieties of H. coronaria. This research done from September 2015-January 2016. This study used qualitative method to made detail and systematic description about flowering phase. H.coronaria flowering process consists of flower initation, flower estabilisment and flower development. Flower initation needs 13-15 days, flower estabilisment needs 10-12 days and flower development consists of early blooming process, full blooming and senescene. Early blooming process needs 1-3 days, full blooming needs 5-12 days and senescene needs 1-3 days. During the development process changes from rounded to pentagonal shape and there is a change in size. The observation result showed that 5 varieties are different from one another based on the difference between the colors of the flowers. Variety 1 has yellow corolla without honey line and deep pink corona. Variety 2 has light yellow green corolla with strong pink honey line and moderate red corona. Variety 3 has moderate red corolla with moderate red honey line and moderate red corona. Variety 4 has light yellow green corolla with moderate pink honey line and light yellow green corona. Variety 5 has moderate red without honey line and grayish red corona